Deregulation of Downstream Oil Sector and Social Welfare in Nigeria, 2010-2022 - Chris , Osita Nebechi; Ifedi, Francisca Obiageli (University of Nigeria Journal of Political Economy, 2024)
The study examines the impact of removal of subsidies on petroleum products on social welfare in Nigeria. Appalling levels of corruption in the management of petroleum subsidy arising from institutional decay and poor policy choices are highlighted. Documentary method was used to generate the relevant secondary data, while the rentier state theory was employed to x-ray the relegation of social welfare arising from the withdrawal of subsidies on petroleum products and corresponding increments in their pump prices attendant to the implementation of neoliberal reforms. The study holds the view that the mismanagement of oil wealth has led to social decay and disempowerment of the masses. The study argues that removal of subsidies on petroleum products by the Nigerian government is in conformity with the on-going determination by the major purveyors of monopoly capitalism to transform the character of state. The study sees responsible political leadership as the only way to actualize prudent management of oil wealth, human security, and sustainable national development in Nigeria.